Patterns of handling Pola Penanganan Masalah Ketertiban Dan Keamanan Oleh Jaga Warga Di Kapanewon Tanjungsari - Arlan Saris Penjalang; Sri Widayanti (Nakhoda: Jurnal Ilmu Pemerintahan, 2025)
Order and security are fundamental elements of sustainable regional development. In the Kapanewon Tanjungsari region, Gunungkidul Regency, D.I Yogyakarta, challenges to social stability arise due to complex demographic, geographic, and socio-economic dynamics. The local government has responded to these conditions by launching the Jaga Warga program, a community-based initiative that aims to increase community participation in maintaining order and security in the neighborhood. This study aims to identify and analyze the patterns of order and security issue handling carried out by Jaga Warga as a form of active community participation. Using a qualitative approach with a case study method, data was collected through field observations, in-depth interviews with various stakeholders, and analysis of activity documentation. The results of the study show that Jaga Warga adopts a community-based communication pattern, establishes intensive coordination with village officials, and implements preventive strategies rooted in local values such as mutual cooperation, deliberation, and social solidarity. This pattern has proven to be effective in increasing community awareness, strengthening social bonds, and creating a collective sense of security. In addition, the success of the Jaga Warga program is influenced by the structural support of the village government and the active participation of residents in neighborhood security activities. This study recommends strengthening Jaga Warga's institutional capacity through training, funding, and a continuous evaluation system, as well as the need for local government policy support to ensure the sustainability of participatory security practices at the local level